Sculptured Surface Design and Implementation by Lofting Design Method Using Cross-sectional B-Spline Curves - Hamdan, Wisam Kadhum; Abdulrazaq, Mustafa Mohammed (Al-Khwarizmi Engineering Journal, 2019)
This research presents a particular designing strategy for a free form of surfaces, constructed by the lofting design method. The regarded surfaces were created by sliding a B-spline curves (profile curves), in addition to describing an automatic procedure for selective identification of sampling points in reverse engineering applications using Coordinate Measurement Machine. Two models have been implemented from (Ureol material) to represent the different cases of B-spline types to clarify its scope of application. The interior data of the desired surfaces was designed by MATLAB software, which then were transformed to UG-NX9 software for connecting the sections that were designed in MATLAB program and obtaining G-code programs for the models In addition, a virtual machining process was simulated to show the machining pitfalls, using VERICUT software.  The samples were machined using 3-axis vertical CNC machine (Isel) type. Finally, the samples were measured using Faro arm (CMM inspection) and it was found that the average of errors was equal to (0.0589 mm) for the cross-sectional uniform B-spline model, and (0.1337 mm) for the lofted non-uniform B-spline model. It can be concluded that the whole steps task which built in the present research can be programmed in a single block of the part program where any surface at minimum designing time can be created from it.